Determination of the available acid-generating potential of waste rock, part I: Mineralogical approach. (December 2018) - Elghali, A.; Benzaazoua, M.; Bouzahzah, H.; Bussière, B.; Villarraga-Gómez, H.
Abstract: Significant volumes of waste rock are produced in mining operations, particularly in open pit operations. Waste rock is characterized by a high heterogeneity in their mineralogical, hydrogeological, and physical properties, especially in comparison to tailings. The purpose of this study was to develop an improved method to quantify the net acid-generating potential of waste rock by incorporating the degree of liberation of acid-generating and neutralizing minerals. Three lithologies were sampled immediately after waste rock blasting. Each lithology was separated into seven fractions: D < 0.053 mm, 0.053 mm < D < 0.3 mm, 0.3 mm < D < 0.85 mm, 0.85 mm < D < 2.4 mm, 2.4 mm < D < 5 mm, 5 mm < D < 15 mm, 15 mm < D < 50 mm; particles >5 cm were not considered. Mineralogical and chemical characterizations showed that sulphides, mainly pyrite, were enriched in the fine to mid-sized fractions (between 0.053 mm and 0.85 mm), and carbonates, mainly calcite, decreased as the particle size increased. Sulphides were more liberated within the fine fractions and their liberation was considered negligible at sizes >2.4 mm. For coarser fractions (>5 mm), sulphides were associated with non-sulphide gangue minerals which was confirmed by micro-computed tomography. The waste rock samples were submitted to both acid base accounting (ABA) and net acid generation (NAG) tests to evaluate their acid-generating potentials. Sixteen size fractions were non-acid generating and five were classified as uncertain. However, standard ABA and NAG tests are based on pulverized samples that don't consider the initial textures of samples. Therefore, ABA results (acid-generating potentials and neutralization potentials) were corrected using the degrees of sulphide and carbonate liberation. The corrected classifications reduced the acid-generating potential of most of the uncertain samples due to the high carbonates content in relation to sulphides. This study also defines a parameter, the diameter of physical locking of sulphides, that can be used to separate waste rock into a reactive and non-reactive fraction based on the relationship between sulphide liberation and particle-size fraction. The reactive fraction refers to waste rock likely to require active acid rock drainage (ARD) management, whereas non-reactive fraction refers to waste rock likely not require active management. Highlights: Sulphides are mainly enriched in the fine to mid-sized fraction. Sulphides were more liberated within the fine fractions and their liberation was negligible at size >2.4 mm. Sulphide and carbonate liberations are used to correct AP and NP of pulverized samples to consider the initial texture of samples. Diameter of physical locking of sulphides separates a waste rock into two fractions with different reactivities.